MANAGEMENT OF STATE-OWNED FIXED ASSETS (BMN) IN THE MINISTRY OF LAW AND HUMAN RIGHTS ENVIRONMENT OF THE RIAU ISLANDS (KEPRI) - Juita Siti Rahayu; Lubna Salsabila (Jurnal Scientia, 2023)
This research is motivated by the condition where the inventory of State-Owned Fixed Assets (BMN) has not been well documented according to the applicable regulations in government ministries/agencies, making it a target for the arrangement and organization of State-Owned Fixed Assets (BMN). The research objective is to determine the Implementation of State-Owned Fixed Asset (BMN) Management in the Ministry of Law and Human Rights Environment. This qualitative descriptive research uses both secondary and primary data, with research informants being several staff members from various divisions. The results of this research describe the implementation of State-Owned Fixed Asset (BMN) management, which is carried out by delegating authority and responsibility for BMN management to the Authorized User of Goods, guidance by leadership regarding usage guidelines and asset management, as well as supervision and control of BMN along with reporting on the management and use of goods. It also involves updating and improving the information system for the BMN section and monitoring internal control carried out by leaders, the Supreme Audit Agency (BPK), and the General Inspectorate.